Pemanfaatan Aplikasi Microsoft Teams sebagai Media Pembelajaran Daring dalam Program Tahfidz Siswa Kelas 6 Sekolah Dasar Islam Terpadu Assaidiyah - Irennisa Aulia Firdaus; Dedih Surana (Bandung Conference Series: Islamic Education, 2022)
Abstrack. This research is about how to use a digital application for learning tahfidzul Qur'an, as a result of the outbreak of the covid-19 virus and causing human activities around the world to turn completely digital and online. This includes the tahfidz class at an Islamic boarding school by utilizing the team's application Microsoft as an online learning tool. On this basis, this research focuses on "Utilization of the Microsoft Teams Application as an Online Learning Media in the Tahfidz Program for Class 6 Students of SDIT Assaidiyah"The aims of this study are: First, to find out the tahfidz learning method using the Microsoft Teams application. Second, to find out the level of student memorization when using the Microsoft Teams application. Third, to find out the obstacles in using the Microsoft Teams application in the tahfidzul Qur'an program. This research was conducted using qualitative methods through field research with the research subject being a tahfidz Qur'an teacher at SDIT Assaidiyah and the object of the research was a class 6 student at SDIT Assaidiyah. The results of this study are: First, the teaching method used is the Tilawatil and murajaah methods, using the ros tone of Qory Imam from Kuwait Mishary Rashid Alafasy. Technical learning by opening Microsoft Teams and then inviting students and everything goes like the face-to-face learning process. Second, the use of the Microsoft Teams application for memorization classes according to the students did not significantly increase their memorization level, with details of the four students interviewed, only one person considered the use of the Microsoft Teams application to increase their memorization rapidly. Even so, the use of the application Microsoft Teams makes it easier for the teacher to supervise and the level of students' memorization progress. Currently, the majority of students' memorization from class 6 of SDIT Assaidiyah is in juz 30 and 29. Third, the main problem experienced when using the application of Microsoft Teams is the slow network and causes communication between students and teachers to be hampered, so students prefer tahfidz classes to be held face-to-face rather than online. But for online applications, students prefer to use WhatsApp for their application media when depositing their memorization with the teacher. Abstrak. Penelitian ini tentang bagaimana pemanfaatan sebuah aplikasi digital untuk sebuah pembelajaran tahfidzul qur’an, sebagai dampak dari merebaknya virus covid-19 dan menyebabkan aktivitas manusia di seluruh dunia berubah menjadi serba digital dan daring. Termasuk dalam hal kelas tahfidz pada sebuah pesantren dengan memanfaatkan aplikasi Microsoft teams sebagai sarana pembelajaran daring. Atas dasar itu penelitian ini berfokus pada “Pemanfaatan Aplikasi Microsoft Teams Sebagai Media Pembelajaran Daring Dalam Program Tahfidz Siswa Kelas 6 Sekolah Dasar Islam Terpadu Assaidiyah.”Tujuan penelitian ini adalah: Pertama, Untuk mengetahui metode pembelajaran tahfidz dengan menggunakan aplikasi Microsoft Teams. Kedua, Untuk mengetahui tingkat hafalan siswa ketika memakai aplikasi Microsoft Teams. Ketiga, Untuk mengetahui hambatan dalam pemanfaatan aplikasi Microsoft Teams pada program tahfidzul qur’an. Penelitian ini dilakukan dengan menggunakan metode kualitatif melalui penelitian lapangan dengan subjek penelitian adalah guru tahfidz qur’an SDIT Assaidiyah dan objek penelitiannya adalah siswa kelas 6 SDIT Assaidiyah. Hasil Penelitian ini adalah: Pertama, Metode pengajaran yang digunakan adalah metode tilawatil dan murajaah, dengan menggunakan nada ros dari Qory Imam asal Kuwait Mishary Rashid Alafasy. Teknis pembelajaran dengan membuka microsoft teams kemudian mengundang peserta didik dan semua berjalan seperti dengan proses membelajaran tatap muka. Kedua, Penggunaan aplikasi microsoft teams untuk kelas hapalan menurut para siswa tidak terlalu membuat tingkat hapalan mereka meningkat pesat, dengan rincian dari empat siswa yang diwawancarai, hanya satu orang yang menganggap penggunaan aplikasi microsoft teams membuat hapalannya meningkat pesat. Meskipun begitu, penggunaan aplikasi Microsoft Teams membuat pihak guru lebih gampang dalam melakukan pengawasan dan tingkat kemajuan hapalan para siswa. Saat ini mayoritas hapalan para siswa dari kelas 6 SDIT Assaidiyah ada di juz 30 dan juz 29. Ketiga, Masalah utama yang dialami Ketika menggunakan aplikasi Microsoft Teams adalah jaringan yang lambat dan menyebabkan komunikasi antara siswa dan guru terhambat, sehingga siswa lebih menginginkan kelas tahfidz diadakan secara langsung melalui tatap muka dibandingkan daring. Tetapi untuk aplikasi daring para siswa lebih menyarankan untuk menggunakan WhatsApp untuk media aplikasi mereka ketika menyetorkan hapalannya kepada guru.